Assessing the returns to education in Georgia - Tamar Khitarishvili (Levy Economics Institute of Bard College, 2010)
The economic returns to education in transition countries have been extensively evaluated in the literature. The present study contributes to this literature by estimating the returns to education in Georgia during the last transition period 2000-04. We find very low returns to education in Georgia and little evidence of an increasing trend in the returns. This picture contrasts with somewhat higher rates of return to education in the mid-1990s in Georgia and the recent estimates from other transition countries. A further analysis of the shifts in the supply and demand for education sheds light on possible causes. In particular, on the supply side, the decline in the quality of education in the 1990s has negated the improvements in the provision of skills needed by market economies during this period. On the demand side, the expansion of the Georgian economy has taken place in the direction of fields such as public administration and education that employ a highly educated workforce but do not remunerate well. Yet it would be a mistake to conclude that education is not a valuable asset in Georgia. The role of education is largely manifested in its impact on the employability of individuals, an issue that has been overlooked in the transition literature. Once this impact is taken into account, education is shown to play an increasingly important role in influencing the earnings of the working population in Georgia. The paper uses the ordinary least squares approach, instrumental variables approach, and sample selection correction, taking into account conditional and unconditional marginal effects of education on earnings.
Keywords: I21; J24; P2; 330; returns to education; human capital; sample selection; instrumental variables; transitional economies; Georgia; Bildungsertrag; Bildungsinvestition; Bildung; Bildungspolitik; Georgien